To solve the equation, we will first distribute the 2/3 to the terms inside the parentheses:
2/3 (x - 6) = 14
2/3 * x - 2/3 * 6 = 14
Multiply 2/3 by 6:
2/3 * x - 12/3 = 14
Simplify the left side of the equation:
(2/3)x - 4 = 14
Add 4 to both sides:
(2/3)x = 18
To isolate x, we need to multiply both sides of the equation by the reciprocal of 2/3, which is 3/2:
(3/2)(2/3)x = (3/2)(18)
The 2/3 and the 3/2 cancel out on the left side, leaving:
(2/1)x = 27
Simplify the left side:
2x = 27
Finally, divide both sides by 2 to solve for x:
2x/2 = 27/2
Simplify:
x = 27/2
Thus, the solution is x = 27/2.
Solve 2/3 (x- 6)=14
1 answer